2022
DOI: 10.5114/aoms/151770
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic antitumor effects of 5-FU and Apatinib on papillary thyroid cancer in vitro and in vivo

Abstract: IntroductionPapillary thyroid carcinoma (PTC) is the most common type of thyroid malignancy with increased incidence rapidly occurring in most countries. The study aimed to investigate the antitumor effects of the combination of 5-FU and Apatinib on PTC.Material and methodsTPC-1 and SW579 cells were treated with 5-FU, Apatinib, or a combination of 5-FU and Apatinib. Cell viability was assessed by the CCK-8 assay. Edu staining and colony formation were used to evaluate the cell proliferation ability. Flow cytom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Studies conducted on SKOV-3 cells indicated the effect of FIS by increasing tumor cell apoptosis, suppressing proliferation, and inhibiting anti-angiogenic activity [158,172]. Studies conducted with the use of FIS and a caspase inhibitor (z-VAD) indicate a decrease in apoptosis occurring in the FIS environment after the use of the inhibitor.…”
Section: Effect Of Fisetin On Ovarian Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Studies conducted on SKOV-3 cells indicated the effect of FIS by increasing tumor cell apoptosis, suppressing proliferation, and inhibiting anti-angiogenic activity [158,172]. Studies conducted with the use of FIS and a caspase inhibitor (z-VAD) indicate a decrease in apoptosis occurring in the FIS environment after the use of the inhibitor.…”
Section: Effect Of Fisetin On Ovarian Cancermentioning
confidence: 99%
“…The authors showed a significant contribution of KEM to cell cycle arrest in the G2/M phase by increasing the expression of p21 and inactivating the Cdc25C and Cdc2 proteins in the Chk2/Cdc25C/Cdc2 pathway and the Chk2/p21/Cdc2 pathway in A2780/CP70 cells (Figure 3). However, the Chk2 receptor is not directly involved in KEM-induced apoptosis and, instead, mediates an intrinsic pathway with the p53 protein and an extrinsic pathway via the upregulation of DR5 and Fas Caspase-3 and caspase-9 Induced apoptosis [158] OVCAR-3…”
Section: Bax Induced Apoptosis [158]mentioning
confidence: 99%